The types of Osteoglossum formosum Müller & Schlegel, 1840 (Teleostei, Osteoglossidae) - van Oijen, Martien J.p.; van Der Meij, Sancia E.t. (Zootaxa, 2013)
The designation of a neotype for Scleropages formosus (Müller & Schlegel, 1840) by Pouyaud et al. (2003) triggered a search for the type specimens of the species, which were found in the collections of the Naturalis Biodiversity Center, Leiden (RMNH) and the Natural History Museum, London (BM(NH)). The publication date of the species is corrected. Moreover, detailed data on the day of capture and the type locality were uncovered. An English translation of the major part of the original Dutch description is provided, and a number of neglected colour descriptions and figures of S. formosus are discussed. Lastly, a lectotype is designated.